Experiencias Pedagógicas entre Discapacidad, Infancia y Matemáticas - Amaya-Gil, Marvin; Patiño-Benavides, Angie; Marín-Pineda, Julieth (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article aims to identify the conditions that strengthen the recognition of single-digit numbers, the basis of mathematical thinking in a nine-year-old student with intellectual disability, who has difficulty in cognitive processes of attention, memory and language, because it is limited for her age, does not follow instructions, her learning is short term and is dependent on the performance of daily activities and is currently in third grade at Técnico Bellas Artes Educational Institution, in the city of Sogamoso (Boyacá).  This study presents a qualitative methodology as its approach and a case study research design and was developed with the approval of the Institution, the assent and consent of the minor and her mother.  The instruments used were semi-structured interviews with the teacher, the psychologist who periodically visits the institution and the minor´s mother; the Individual Plan for Reasonable Adjustment Plan (RAP) was also considered; moreover, the process developed in each session provides evidence from field diaries, which were observed and reported in detail. The results allowed us to identify that learning is strengthened through interaction and cooperativism with peers; also, the teacher role is fundamental in providing interactive stimuli, didactic resources, making reasonable adjustments, promoting a positive learning environment, and providing needed supervision; all which allowed the child to advance in her formative process of strengthening the learning of single-digit mathematical quantities, from the number 0 to 9;  It's also worth noting the importance of teacher/student supervision, regardless of the orientation made during the formative process of students diagnosed with intellectual disabilities.